Evaluasi Program Penyelengaraan Pesta Paduan Suara Gerejawi Tingkat Provinsi Sumatera Selatan - Panjaitan, Bagus Ade Dinata; Lisdiana, Lisdiana; Syuroh, Mat (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2024)
The Ecclesiastical Choir Party Development Institute is an organization/institution tasked with developing the Regional Ecclesiastical Choir Party Development Institute (LPPD) and improving the quality of ecclesiastical choirs in collaboration with churches in Indonesia.This research aims to determine the process of organizing ecclesiastical choir parties (Pesparawi) at the South Sumatra provincial level and to find out the problematic factors that hinder and support the process of organizing ecclesiastical choir parties (Pesparawi) at the South Sumatra level. This research uses qualitative research. The collection techniques used by researchers to reveal or capture qualitative information and respondents according to the scope of the research are: interviews, observation and documentation. The results of this research show that the activities for organizing the Ecclesiastical Choir Festival (Pesparawi) at the South Sumatra Province level in terms of each indicator such as resources, facilities and infrastructure as well as budget funds are still not good and need to receive attention, while the organizational structure and implementation of the competition is good. This can be seen from the results of interviews, observations and documentation carried out by the author that the activities for organizing Ecclesiastical Choir Festivals (Pesparawi) at the South Sumatra Province level are good with several improvements and commitments from the Provincial Government in supporting each program of the Ecclesiastical Choir Festival Development Institute.